Edonismo, sentimentalismo morale e riflessione emotiva. Husserl e la storia del dibattito in etica - Poltronieri, Alessandro (Bollettino Filosofico, 2024)
Husserl had never hidden the essentially ethical connotation of phenomenological practice. Since it is configured as an attitude, phenomenology cannot ignore the ethical dimension in which it is necessarily inscribed. The same goes for history: before being an objectum with which the phenomenologist must deal, history is a dimension in which the phenomenologist carries out his research. Therefore, it is fruitful to look at the investigation that Husserl pursues on the history of ethics. In the introduction to ethics course of 1920-24 Husserl tackles hedonism and moral sentimentalism. Both perspectives have seen, without becoming authentically aware of it, the transcendental role played by feeling acts [Gemütsakte] with respect to the axiological sphere. Husserlian phenomenology aims to bring this discovery to consciousness, showing its advantages in ethical debate. Keywords: Ethics, Hedonism, History, Husserl, Sentimentality